2024
DOI: 10.1002/rmv.2515
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, clinical efficacy and safety of additional second COVID‐19 booster vaccines against Omicron and its subvariants: A systematic review

Santenna Chenchula,
Madhu Bhargavi Chandra,
Madhu Babu Adusumilli
et al.

Abstract: The Omicron variant of severe acute respiratory syndrome coronavirus 2 is a new variant of concern (VOC) and an emerging subvariant that exhibits heightened infectivity, transmissibility, and immune evasion, escalating the incidence of moderate to severe coronavirus disease 2019 (COVID‐19). It resists monoclonal antibodies and diminishes vaccine efficacy. Notably, new sublineages have outpaced earlier predominant sublineages. Although the primary vaccination series and initial boosters were robust against prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…COVID-19 boosters in these individuals aim to reduce their occupational risk of infection and transmission to vulnerable populations. Bivalent boosters may provide protection against hospitalisation and severe symptoms caused by various SARS-CoV-2 variants [ 7 , 8 , 26 , 27 , 28 ], particularly in individuals with “hybrid immunity” [ 1 , 2 , 3 , 4 , 5 , 7 , 8 ]. Such boosters can enhance both humoral and cellular immunity, decrease infection rates, and offer protection, especially for specific populations such as organ transplant recipients, dialysis patients, individuals with chronic renal disease, the elderly population, and immunocompromised individuals [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…COVID-19 boosters in these individuals aim to reduce their occupational risk of infection and transmission to vulnerable populations. Bivalent boosters may provide protection against hospitalisation and severe symptoms caused by various SARS-CoV-2 variants [ 7 , 8 , 26 , 27 , 28 ], particularly in individuals with “hybrid immunity” [ 1 , 2 , 3 , 4 , 5 , 7 , 8 ]. Such boosters can enhance both humoral and cellular immunity, decrease infection rates, and offer protection, especially for specific populations such as organ transplant recipients, dialysis patients, individuals with chronic renal disease, the elderly population, and immunocompromised individuals [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both mRNA vaccine groups showed significant increases in neutralising antibodies (nAb) and T-cell responses after the fourth dose (7.32, 95% CI, 3.24–16.54; 6.22, 95% CI, 3.90–9.92). The study also reported that Spikevax induced higher antibody (Ab) titres than Comirnaty Original after the fourth dose [ 6 , 7 ].…”
Section: Current German Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations